Social play experience in juvenile rats is indispensable for appropriate socio-sexual behavior in adulthood in males but not females - Marquardt, Ashley E.; VanRyzin, Jonathan W.; Fuquen, Rebeca W.; McCarthy, Margaret M. (Frontiers in Behavioral Neuroscience, 2023)
Social play is a dynamic and rewarding behavior abundantly expressed by most mammals during the juvenile period. While its exact function is debated, various rodent studies on the effects of juvenile social isolation suggest that participating in play is essential to appropriate behavior and reproductive success in adulthood. However, the vast majority of these studies were conducted in one sex only, a critical concern given the fact that there are known sex differences in play’s expression: across nearly all species that play, males play more frequently and intensely than females, and there are qualitative sex differences in play patterns. Further limiting our understanding of the importance of play is the use of total isolation to prevent interactions with other juveniles. Here, we employed a novel cage design to specifically prevent play in rats while allowing for other forms of social interaction. We find that play deprivation during the juvenile period results in enduring sex-specific effects on later-life behavior, primarily in males. Males prevented from playing as juveniles exhibited decreased sexual behavior, hypersociability, and increased aggressiveness in adulthood, with no effects on these measures in females. Importantly, play deprivation had no effect on anxiety-like behavior, object memory, sex preference, or social recognition in either sex, showing the specificity of the identified impairments, though there were overall sex differences in many of these measures. Additionally, acute play deprivation impaired performance on a test of prosocial behavior in both sexes, indicating a difference in the motivation and/or ability to acquire this empathy-driven task. Together, these findings provide novel insight into the importance and function of juvenile social play and how this differs in males and females.